Soil carbon and nitrogen changes due to soil particles redistribution caused by photovoltaic array - Zhao, Feiyan; Meng, Zhongju; Liu, Yang; Li, Peng; Tang, Guodong (Frontiers in Environmental Science, 2025)
There is an inevitable relationship between the size of soil particles and the distribution of organic matter. The soil texture in desert photovoltaic areas is poor, with variations in soil particle size and organic matter. This study explores the heterogeneity of soil particle size and organic matter distribution at different zonal scales, aiming to clarify the impact of photovoltaic array construction on microtopography and, consequently, on these indicators. This will facilitate precise vegetation restoration based on the distribution of nutrients within the region. Baced on the Kubuqi Desert photovoltaic area as the research area, the soil particle size in the 0–30 cm soil layer and the distribution of soil organic matter in the main particle size range (<250 μm, <500 μm) in this area were analyzed. Fine sand (particle size 100–250 μm) was the main component of the soil; the carbon and nitrogen stocks in the upper 0–30 cm of soil diminished linearly with escalating wind speed gradient, from 70.76 Mg C ha−1 to 53.82 Mg C ha−1 and from 13.96 Mg N ha−1 to 8.12 Mg N ha−1. The total carbon and nitrogen levels in the two soil particle sizes, together with their contribution to total soil organic carbon, diminished as the wind speed gradient intensified, with the reduction in organic carbon content becoming stronger. The organic carbon content of soil particles <250 μm accounted for 63.7%–98.6% of the total soil organic carbon, while that of particles 250μm–500 μm only accounted for 3.32%–33.34%. SOC was significantly higher in the 0–5 cm layer than in the 5–30 cm layer in all areas of the photovoltaic array. Wind causes changes in sand particle transport in PV arrays, and may also alter the microclimate environment leading to differences in soil decomposition cycling processes, which can exhibit uneven organic carbon and nitrogen distribution between particles. Our research demonstrates the internal distribution of soil carbon and nitrogen reserves in each region of the photovoltaic array, establishing a robust foundation for subsequent vegetation restoration and plant species selection in each region, thereby implementing the “photovoltaic + ecological” governance model.